Internal Control and Its Impact on the Accounting Management of Small Companies in the Service Sector in Peru. Case Study - 2023 - Gonzales Renteria, Yuri Gagarin; Garcia Saldana, Sixto; Síchez Muñoz, Víctor Alejandro; Gonzales Flores, Diana Yurisel (Journal of Ecohumanism, 2025)
Internal control provides the actions, plans, policies, procedures and methods that contribute to the continuous improvement, operational, financial and economic efficiency of the entity, together with the achievement of its established objectives; Therefore, the research had as objective : to determine as he control internal affects in the management accountant of the company A1 International Investments EIRL-Lima, 2023. The methodology used was qualitative, descriptive, non-experimental, bibliographic and case design; the technique of bibliographic review and interview were applied as instruments . bibliographical and a questionnaire . The results showed that internal control significantly affects the favorable development of accounting management; from the recording of financial transactions to the analysis of financial information . Accounting management collects , records, analyzes and interprets financial information, which is an essential tool for making informed decisions for the benefit of organizations. Through solid control, accounting management will be developed in order to ensure the protection of assets, the reliability of financial information, the validity of accounting records and systems and compliance with current laws and regulations. According to the results, it was concluded that it is necessary to establish a permanent internal control system in conjunction with its components, designed according to the specific needs of the company under study, to correct the deficiencies of the empirical controls used.